1994
DOI: 10.1007/bf00058976
|View full text |Cite
|
Sign up to set email alerts
|

Five years of experience with biodegradable implants in paediatric surgery

Abstract: After successful animal research on minipigs and calves, it was decided in January 1988 to begin the clinical application of PLLA (poly-L-lactide) threaded plugs, nuts and woven bands made of PDS (poly-dioxanon). The implants were made of pure crystalline 1-1-PLLA with an average molecular weight between 220000 and 500000 I.E. Mechanical testing revealed a Young's modulus of 4000 N mm -2, a fracture elongation of 2%, and strength values under tension and compression and bending of 55, 110 and 120 N mm -2, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…The remaining twenty-four articles were clinical studies. Eight studies were stated as prospective [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] and another eight were stated as retrospective [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ], while the design of the other eight was not specified [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining twenty-four articles were clinical studies. Eight studies were stated as prospective [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] and another eight were stated as retrospective [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ], while the design of the other eight was not specified [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the criteria used here, it is possible that a mild FBR was present, which would add another 9.86% to this category. In Illi et al (1994), histology was performed only after the implant had been completely absorbed [83]. Since FBR ceases once the PLLA is degraded, mild FBR may have existed before.…”
Section: Discussionmentioning
confidence: 99%
“…Bioresorbable materials are also used in paediatric orthopaedics [45,[129][130][131][132][133]. Svensson et al [45] reported the use of biodegradable osteosynthetic materials in 50 children with transphyseal or osteochondral fractures.…”
Section: Clinical Employments Of Bioresorbable Implantsmentioning
confidence: 99%
“…Two patients had non-union of articular radial head fractures, possibly related to a foreign-body reaction. Illi et al [132] evaluated the efficiency of PLLA implants in 32 children, aged 11 months to 17 years, with 15 cases of craniofacial malformations, 16 cases of neurotraumatological lesions and 1 case of refixation of an osteochondral flake of the patella. The follow-up time ranged from 3 months to 5.6 years, with an average of 3 years.…”
Section: Clinical Employments Of Bioresorbable Implantsmentioning
confidence: 99%